Diabetes and its negative impact on outcomes in orthopaedic surgery - Wukich, Dane K (World J Orthop, 2015)
An estimated 285 million adults (aged 20-79 years) worldwide were diagnosed to have diabetes mellitus (DM) in 2010, and this number is projected to grow to 439 million adults by the year 2030. Orthopaedic surgeons, regardless of their subspecialty interest, will encounter patients with DM during their career since this epidemic involves both developed and emerging countries. Diabetes results in complications affecting multiple organ systems, potentially resulting in adverse outcomes after orthopaedic surgery. The purpose of this review is to discuss the pathophysiology of DM and its potential for impacting orthopaedic surgery patients. Diabetes adversely affects the outcome of all orthopaedic surgery subspecialties including foot and ankle, upper extremity, adult reconstructive, pediatrics, spine surgery and sports medicine. Poorly controlled diabetes negatively impacts bone, soft tissue, ligament and tendon healing. It is the complications of diabetes such as neuropathy, peripheral artery disease, and end stage renal disease which contributes to adverse outcomes. Well controlled diabetic patients without comorbidities have similar outcomes to patients without diabetes. Orthopaedic surgeons should utilize consultants who will assist in inpatient glycemic management as well as optimizing long term glycemic control.